Implementing Creative Learning with Technology to Improve Literacy and Numeracy in Primary Schools - Anggun, Mei Sekar; Fakhruddin, Fakhruddin; Arbarini, Mintarsih; Subali, Bambang; Widiarti, Nuni (Journal of Innovation and Research in Primary Education, 2025)
Literacy and numeracy skills are important foundations that determine students' academic success at the primary school level. However, their achievement is still facing obstacles, mainly due to limited access to technology and the dominance of traditional learning methods. The purpose of this literature review is to evaluate the effectiveness of implementing technology-based creative learning in improving literacy and numeracy competencies through a Systematic Literature Review (SLR) approach of 25 selected journals, consisting of 15 international and 10 national journals published in the last five years, from 2019 to 2024. The literature search process was conducted through Scopus, ERIC, Google Scholar, Sinta, and Garuda databases using keywords such as creative learning technology, numeracy digital literacy, and basic education. Journal selection was done systematically based on inclusion criteria, namely: (1) relevance to the topic of numeracy-literacy in basic education, (2) containing elements of technology use in the learning process, (3) based on empirical or experimental research, and (4) available in full access. The journal quality evaluation used the CASP (Critical Appraisal Skills Programme) approach to assess clarity of purpose, methodology and validity of findings. The results of this literature review show that the use of technologies such as gamification, augmented reality (AR) and adaptive platforms can increase student engagement by up to 80%, strengthen understanding of literacy and numeracy concepts between 25-40%, and hone collaborative and critical thinking skills by 35-50%. The most successful implementation strategies include the integration of technology in problem based learning projects and the use of personalised learning apps, which have been shown to consistently improve learning outcomes across different school contexts. However, the implementation of these strategies is still constrained by structural issues, such as limited digital infrastructure with only 30% of schools in remote areas having stable internet access and low teacher preparedness, where around 45% of teachers do not have adequate training in the use of advanced technology. The conclusion of this article states that technology-based creative learning approaches have the potential to be effective innovative solutions, provided they are supported by adequate infrastructure, continuous teacher training and the implementation of hybrid learning models that combine technology with local context based approaches. Policy recommendations are directed at developing offline learning modules for remote areas and strengthening further research based on local wisdom.